Change of the glaciation dimensions in the basins of Malaya Laba and Belaya Rivers (West Caucasus) for the last hundred years - Yu. V. Efremov; Yu. G. Ilyichev; A. V. Zimnitsky (Лëд и снег, 2015)
Changes in area of glaciation and quantity of individual glaciers in basins of rivers Malaya Laba and Belaya (West Caucasus) are investigated. The Glacier Inventories of 1911 [19] and 1967 [10] and space imagery for 2000–2012 are used as the base materials. Sizes of some glacier were corrected in field studies by GPS positioning and ground theodolite surveys. It was determined that, like in many other glacier basins of the Great Caucasus, the glaciations in this region decreased. For the period of 1902/1906–2013 the glaciations area reduced by 12.0 km2 (or by 43.8%). For the same period the glacier quantity decreased by eight (11.8%), and in 2013 sixty glaciers remained. According to calculations, mean annual rate of the glacier retreat amount to about 2 m. Small glaciers and snow patches remain in places of melted glaciers which keep some properties of glaciers (so called firn glaciers).